On the use of private versus social information in oviposition site choice decisions by Drosophila melanogaster females. (18th March 2020) - Malek, Heather L; Long, Tristan A F
Abstract: Individuals are faced with decisions throughout their lifetimes, and the choices they make often have important consequences toward their fitness. Being able to discern which available option is best to pursue often incurs sampling costs, which may be largely avoided by copying the behavior and decisions of others. Although social learning and copying behaviors are widespread, much remains unknown about how effective and adaptive copying behavior is, as well as the factors that underlie its expression. Recently, it has been suggested that since female fruit flies ( Drosophila melanogaster ) appear to rely heavily on public information when selecting oviposition sites, they are a promising model system for researching patch-choice copying, and more generally, the mechanisms that control decision making. Here, we set out to determine how well female distinguish between socially produced cues, and whether females are using "relevant" signals when choosing an oviposition site. We found that females showed a strong preference for ovipositing on media patches that had been previously occupied by ovipositing females of the same species and diet over other female outgroups. However, in a separate assay, we observed that females favored ovipositing on media patches that previously housed virgin males over those exhibiting alternative conspecific signals. Our results confirm that females use cues left behind by other flies when choosing between potential oviposition sites, though their prioritization of these signals raises serious questions as to whether fruit flies are employing copying behavior, or are instead responding to signals that may not be of relevance to oviposition site suitability. Abstract : In many species, individuals base their behavioral decisions on the choices made by other individuals. Fruit flies, Drosophila melanogaster, have been suggested as a model for examining the phenomenon of copying behavior regarding egg-laying site choice. In this study, we tested the assumption that female flies use relevant public cues when copying as there are potential costs of maladaptive. We found that females strongly based their egg-laying behavior on the cues deposited by others, but that this does not necessarily mean that they are copying.